PENGARUH PENAMBAHAN EKSTRAK KAYU SECANG (Caesalpinia sappan L.) DAN MINYAK IKAN LEMURU SEBAGAI ADITIF PAKAN TERHADAP DAYA SIMPAN TELUR DAN KOLESTEROL TELUR PUYUH - Liana Indah Lestari; Anang Widigdyo; Nita Opi Arikustanti (AVES: Jurnal Ilmu Peternakan, 2017)
This research aimed is to determine the effect of Secang extract addition and sardinella fish oil as feed additive on eggs performance and production of quail. The 98 quails and 10 weeks divided into 4 groups with unequal replication using the completely randomized design. The treatment which are P0 (based ration), P1 (based ration + 0,2% secang extract + 4% sardinella fish oil), P2 (based ration + 0,4% secang extract + 4% sardinella fish oil), P3 (based ration + 0,6% secang extract + 4% sardinella fish oil). The parameters observed were length storage time of egg, egg cholesterol rate. Data were analyzed by ANOVA and Duncan ’s analysis. The results showed that Secang extract addition and sardinella fish oil were increase egg cholesterol (P<0.05) and not significantly (P>0.05) on length storage time of egg and production of quail. Keywords: Caesalpinia sappan L., egg cholesterol, Sardinella fish oil.